Religion, land and politics: Shrines and literacy in Punjab, Pakistan - Malik, Adeel; Mirza, Rinchan Ali (International Food Policy Research Institute, 2015)
This paper empirically examines the impact of religious shrines on development. Compiling a unique database covering the universe of shrines across Pakistani Punjab, we explore whether the presence of holy Muslim shrines helps to explain regional variation in literacy rates. Our results demonstrate that the presence of shrines adversely affects literacy only in regions where shrine-related families have a direct political influence. Shrines in these regions represent the confluence of three resources—religion, land and politics—that together constitute a powerful structural inequality with potentially adverse consequences for development. We also probe the determinants of political selection, and find that shrines considered important in the British colonial assessment were more likely to select into politics in post-partition Punjab.